2021
DOI: 10.1186/s12870-020-02755-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plastid biogenesis leading to the formation of albino regenerants in barley microspore culture

Abstract: Background Microspore embryogenesis is potentially the most effective method of obtaining doubled haploids (DH) which are utilized in breeding programs to accelerate production of new cultivars. However, the regeneration of albino plants significantly limits the exploitation of androgenesis for DH production in cereals. Despite many efforts, the precise mechanisms leading to development of albino regenerants have not yet been elucidated. The objective of this study was to reveal the genotype-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 102 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…In the current diallel, the rpoC1 and matK (position: 2099) co-segregate and this matK/rpoC1 haplotype is significantly associated with DTF under AT and HT (P <0.0001) but not with the clock traits. However, another member of the PEP complex (Hess et al, 1993; Gajecka et al, 2021), i.e. rpoC2 , appeared as a significant QTLs for several growth and reproductive traits.…”
Section: Resultsmentioning
confidence: 99%
“…In the current diallel, the rpoC1 and matK (position: 2099) co-segregate and this matK/rpoC1 haplotype is significantly associated with DTF under AT and HT (P <0.0001) but not with the clock traits. However, another member of the PEP complex (Hess et al, 1993; Gajecka et al, 2021), i.e. rpoC2 , appeared as a significant QTLs for several growth and reproductive traits.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of genotype on the occurrence of albino plants is more prominent in androgenic cultures of cereals. Albinism in anther cereal cultures was accompanied by various changes that take place in the chloroplast genome, such as the micro-and macro-deletion of photosynthetic and structural plastid-localized genes [58,59] and changes in their copy number [19]. On the other hand, the appearance of the albino phenotype is also controlled by various nuclear-localized genes, without changes in the plastid genome [60].…”
Section: Discussionmentioning
confidence: 99%
“…In barley, it was found that the ability of genotypes to regenerate green plants in androgenic cultures depends on the level of differentiation of microspore plastids in vivo [19]. It has been suggested that the molecular changes leading to the albino phenotype are genetically determined before the introduction of microspores into the in vitro culture [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of granule-bound starch synthase I ( GBSSI ) gene in early-mid microspores correlated with a genotype ability to regenerate green plants via androgenesis [ 194 ]. Results concerning the role of nuclear and plastic-encoded polymerases in albino and green plant regeneration indicating antero- and retrograde phenomenon in barley were presented from the same group [ 195 ]. Research conducted on Arabidopsis thaliana has shown that the transcriptome composition changes significantly during callus induction in plant tissue culture, proving the high dynamics of DNA methylation [ 196 ].…”
Section: Introductionmentioning
confidence: 99%